REVISITING INCULTURATION AND ITS CHALLENGES IN INDIA - Xavier, Joseph (Asian Horizons, 2011)
has received as a gift from God. Unlike other religions, Christianity by its very nature is a faith sharing community. Sharing the Good News is a constituent element of its essence and existence. Therefore mission is not an extraneous element added to the Church. It in fact takes the form of tradition in the Pauline sense—paradosis as traditio (handing over or passing on). That is what Paul affirms when he says, “I handed on to you what I in turn had received” (I Cor 15: 3). Tradition in that sense is “the ongoing self-transmission of the word of God in the Holy Spirit through the service of the Church for the salvation of all humanity.”1 Again, seen from that perspective, mission is not so much of “converting” someone but sharing the Good News so that all may come to the fullness of life (Jn 20: 31). Therefore, all of us are called upon to participate in this missio Dei, the mission of God.2 Had the first disciples kept the faith for themselves and did not pass it on to others, it would have died with them and it would not have reached us. How did they do that? There are different ways of handing on the faith. Inculturation is one of those ways in which the faith is shared and proclaimed. It is significant to note that inculturation is not an entirely new concept in Christianity.